Advanced Public Financial Management Reforms in South East Europe - Pavesic-Skerlep, Mia (IMF Working Papers; Working Paper, 2009)
This paper aims to clarify possible systemic bottlenecks to the introduction of advanced PFM reforms in the SEE countries. It relates key fiscal developments to PFM reform processes over the last 15 years. PFM reform strategies must be realistic, with clear objectives and timetables, and with strong country ownership. Among the advanced reforms, some aspects of medium-term budgeting seems to be somewhat less challenging than performance-oriented budgeting, and it could be rational to make sure that there is solid progress in this area first. When developing performance budgets, countries should consider focusing initial efforts on the areas that are most suitable for performance management, such as education and health.